PERAN GURU DALAM PEMBINAAN PERILAKU BERAGAMA PADA USIA REMAJA: STUDI KUALITATIF NATURALISTIK DI SMA MUHAMMADIYAH 09 BEKASI-TIMUR - Putri, Nurhasanah; ., Supriyanto (Turats, 2012)
The theme of this study on the Role of Teachers in the Development of Religious Behavior in Adolescent Age: Qualitative Naturalistic Studies at SMA Muhammadiyah (Muhammadiyah High School) 09 in East Jakarta. From the study it can be concluded that the role of teachers in fostering religious behavior in adolescence that is giving good examples, cooperation with various parties, both personally and collectively through the elderly, the environment or to perform various religious activities are held such as the following activities: a) inter-school competitions, such as speech, calligraphy, and read verses from the Qur?an. b) Held regular weekly or monthly recitals as pesantren flash, etc. Muhammadiyah high school 09 teen behavior change may be formed as well. Contributing factor in the role of teachers in fostering religious behavior in adolescence is a spirit coaches, parent support, and complete facilities, as well as the inhibiting factor is the youth in the environment around the school